Implications of Agricultural Land Conversion for Sustainable Food Security: Evidence from Vietnam - Irene Vera Purba; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko; Anurat Anantanatorn (Lembaga Contrarius Indonesia, 2025)
Agriculture, as the primary source of food, is increasingly threatened by land-use conversion driven by urbanization, industrial expansion, and economic transformation—particularly in agrarian countries such as Indonesia and Vietnam. This research aims to analyze the patterns and driving factors behind agricultural land conversion in both countries, assess its impact on sustainable food security, and formulate appropriate policy solutions. Employing a normative legal approach combined with policy analysis, this study draws on primary and secondary data, including legal frameworks, academic literature, and national policies. The findings reveal three key insights. First, land-use change is predominantly driven by institutional weaknesses, legal ambiguities, and a pragmatic legal culture that fails to adequately safeguard agricultural land. Second, both countries exhibit similar trends in the conversion of productive farmland to non-agricultural uses, leading to reduced food land availability, ecological degradation, and socio-economic disruptions for farming communities. Third, a policy reconstruction is urgently needed—one that involves harmonized and enforceable regulations, institutional strengthening, and participatory economic mechanisms to ensure land protection. In conclusion, the study emphasizes the critical need for integrated and sustainable policy frameworks to maintain food security, promote environmental sustainability, and uphold social justice in the Southeast Asian region.